2020
DOI: 10.2147/opth.s258817
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inter-Eye Vault Differences of Implantable Collamer Lens Measured Using Anterior Segment Optical Coherence Tomography</p>

Abstract: Purpose The distance between an implantable collamer lens (ICL) and the crystalline lens, namely vault, is a space regulated by the interaction of the ICL and the anatomical structures of the eye. This study analysed the differences in vault size between fellow eyes with similar anterior segment biometry. Patients and Methods A retrospective case series analysed 109 cases of patients bilaterally implanted with EVO-V4c. Patients were analysed pre- and postoperatively usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…10 Manito et al compared the differences of clinical vault between the bilateral eyes, of which nearly 50% of eyes showed the differences higher than 100 μm. 11 They explained that the different intereye clinical vault may be due to the different position of ICL haptic which created different ICL arc. We think the formation mechanism of the clinical vault can be multifactorial, combining the ICL haptic-related parameters may be conducive to our understanding of clinical vault.…”
Section: Discussionmentioning
confidence: 99%
“…10 Manito et al compared the differences of clinical vault between the bilateral eyes, of which nearly 50% of eyes showed the differences higher than 100 μm. 11 They explained that the different intereye clinical vault may be due to the different position of ICL haptic which created different ICL arc. We think the formation mechanism of the clinical vault can be multifactorial, combining the ICL haptic-related parameters may be conducive to our understanding of clinical vault.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the limited number of eyes implanted with 12.6 and 13.7 mm ICLs may have restricted the ability for detecting the influence of ICL size on the vault. Nonetheless, the inter-eye comparisons showed no statistical and no clinical difference (repeatability for vault measurement ∼60 µm [ 38 ]) between sICL and tICL, with the inter-eye differences similar to those observed in fellow eyes implanted with the same ICL geometry [ 16 ]. The current results allow us advancing that the vault prediction for an ICL size is independent of the ICL optical geometry.…”
Section: Discussionmentioning
confidence: 99%
“…The ICL size and power were selected according to the manufacturer recommendations using the online calculator (OCOS™). The preoperative, postoperative and surgical protocol has been described elsewhere by our group [ 16 ]. This research followed the tenets of the Declaration of Helsinki and ethical approval was conceded by the local ethics committee (Comité Ético de Investigación Clínica de Badajoz).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was another common concern for those who had never performed ISBICLS. Previous studies proposed that DSBICLS can be used to adjust the size of the second eye based on vault of the first eye 1 day after surgery, thus decreasing the risk of bilateral ICL size exchange [ 21 , 22 , 30 ]. According to our results, although the percentage of such cases was negatively associated with performing ISBICLS, most surgeons reported that it occurred less than 25% of the time.…”
Section: Discussionmentioning
confidence: 99%